Identity and the Dynamics of Preferences - Davide Dragone; Michele Viviani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
Some recent economic contributions have studied individual identity in terms of explicit choices and social categories to which a person belongs to. According to Social sychology, identity is also the result of a process in.uenced by self-regulation mechanisms. We model endogenous identity-dependent preferences as the dynamic result of two mechanisms: environmental pressure and the persistent effect of past socialization in the adaptation to new environments We apply this model to environments where the agent must tradeoff con.icting utility functions, such as material and non-material payoffs, or self-interest and other-regarding preferences. The model shows that heterogeneity in individual preferences, besides being the result of socialization, cultural transmission and environmental incentives, critically hinges on the feed-back of behaviour on preferences.
Keywords: 330